L. Oviedo, La credibilidad de la propuesta cristiana, Sal terrae, Salamanca 2022, s. 338. - Orłowski, Piotr Paweł (Studia Gdańskie, 2023)
L. Oviedo, La credibilidad de la propuesta cristiana, Sal terrae, Salamanca 2022, s. 338.